The Role of Economic Models and Its Challenges; A Methodological Review of Dani Rodrik’s Economics Rules - Seyed Hossein Mirjalili (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Danny Rodrik’s “Economics Rules” is a book on the methodology of economics that addresses the do’s and don’ts of modeling in economics because, in his view, models make economics a science. Rodrik’s main point in this book is that different social environments require different models, and economists mistake a model with the model. The method of analysis in this review article is analytical, and the aim is to evaluate the content of the book from the perspective of economic methodology. Some challenging issues in the book include ambiguity and amphibology in the title of the book, model reductionism, diversity of models of economic schools, non-model fields of economics, being scientific by method, ambiguity in the concept of critical assumptions, horizontal or vertical progress of economics in macroeconomics, the problem of economics or economists, and the application of Rodrick’s method in the DSGE model in macroeconomics.